2017
DOI: 10.25103/jestr.106.16
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Building Information Modeling in Electrical Systems Design

Abstract: Building Information Modelling (BIM) is an object-oriented approach that can virtually create a 3D digital model of a building capable of doing realistic engineering analysis well before the construction begins. BIM offers sophisticated tools for electrical trade design and estimation. This paper primarily investigates with supportive case studies, the potential applications of BIM in electrical system design and analysis. Further, its energy analysis, geographical scale significance and smart built environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
15
0
4
Order By: Relevance
“…A principal vantagem do BIM em projetos elétricos é a modelagem tridimensional suportada por sistemas de informação semântica de sistemas como iluminação, energia, roteamento de cabos e sistemas de baixa tensão [2]. Essa modelagem pode se beneficiar de cálculos de iluminação, sistemas de energia e roteamento de cabos, projeto e balanceamento de circuitos e quadros, proteção, visualização tridimensional, estimativas de quantidade e custo, detalhamento de pré-fabricação, análise de segurança, comunicação de projeto aprimorada, planejamento de layout [3].…”
Section: Sbtic'21: Inteligência Artificial Construtivaunclassified
“…A principal vantagem do BIM em projetos elétricos é a modelagem tridimensional suportada por sistemas de informação semântica de sistemas como iluminação, energia, roteamento de cabos e sistemas de baixa tensão [2]. Essa modelagem pode se beneficiar de cálculos de iluminação, sistemas de energia e roteamento de cabos, projeto e balanceamento de circuitos e quadros, proteção, visualização tridimensional, estimativas de quantidade e custo, detalhamento de pré-fabricação, análise de segurança, comunicação de projeto aprimorada, planejamento de layout [3].…”
Section: Sbtic'21: Inteligência Artificial Construtivaunclassified
“…They concluded that the engagement in concurrent cocreation and one multidisciplinary model, through a transparent and inclusive process could be the solution of MEP systems' coordination (Akponeware and Adamu, 2017). Farooq et al (2017) investigated with supportive case studies, the potential applications of BIM in electrical system design and analysis, and concluded that seamless integration of semantic information system of BIM with Geographical Information System, GIS can be very useful for electrical grid optimization and city energy modelling. Korman et al (2010) recommended the following order in MEP coordination: HVAC air ductworks, sanitary drainage system, HVAC process piping, fire protection piping, water distribution piping, electrical.…”
Section: Mep Systems Design and Coordinationmentioning
confidence: 99%
“…W zakresie instalacji elektrycznych, optymalizacja i automatyzacja przeprowadzana jest zazwyczaj na bazie dokumentacji Revit API [12]. Istniejące opracowania dotyczą głównie prostych operacji związanych z pobieraniem z modelu cyfrowego informacji dotyczących liczby opraw oświetleniowych i ich parametrów, w szczególności sumarycznej mocy [13]. Natomiast wraz z upowszechnianiem się technologii BIM w środowisku budowlanym, powstają narzędzia optymalizacyjne i automatyzujące prace projektowe.…”
Section: Automatyzacja I Optymalizacja Z Wykorzystaniem Bimunclassified